Formation of the concept of Istiḥsan in Islamic Law - Kayadibi, Saim (IIUM Press, 2011)
The concept of istiḥsān (juristic preference) played a crucial role in intellectual heritage of the history of Islamic law and the development of Islamic legal reasoning through putting human’s contribution into judgments based on primary principles of securing ease and avoiding hardship. In the process of formation of istiḥsān, the concept of qiyās (analogy) was the main factor. When the result of qiyās would cause hardship to the people, the concept of istiḥsān was applied giving preference to unconsidered evidence which may eradicate hardships. No technical definition of istiḥsān have reached us from the very early Islamic legal history, despite the notion of istiḥsān has been used throughout the history of formation of Islamic law. This paper intends to investigate empirically the historical journey of istiḥsān which was applied researching its traces throughout the history of Islamic legal reasoning and critically discuss their applications in Islamic law giving special emphasis on relationship with the concept of qiyās.